Pengaruh Model Pembelajaran Flipped Classroom Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas IV Sekolah Dasar - Sri Imawati; Dwi Meliyana; Nidar Yusuf; Gunawan Santoso (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2022)
This research is motivated by the low ability to understand students' mathematical concepts in flat shape materials and the lack of teacher innovation in choosing learning models, so that students feel bored in the learning process. The purpose of this study was to determine whether or not there was an influence of the Flipped Classroom learning model on students' ability to understand mathematical concepts and at the same time to determine the magnitude of this influence. This study used a quantitative approach with a pre-experimental method with a one group pretest-posttest design. The population of this study were fourth grade students at SDN Perigi 01, totaling 89 students, with a sample of 31 students. Data collection techniques using observation, tests and documentation. Data analysis was performed using the Paired-Sample T-test with a significance level of 0.05 (5%). The results of this study indicate that there is an influence of the Flipped Classroom model on students' ability to understand mathematical concepts. The results of the hypothesis testing that has been carried out show that the significant value obtained is 0.000 <0.05. The percentage gain obtained was 33.7%. So it can be concluded that there is an influence of the Flipped Classroom model on the ability to understand mathematical concepts of fourth grade elementary school students by 33.7%.